Open‐Circuit Voltage in Organic Solar Cells: The Impacts of Donor Semicrystallinity and Coexistence of Multiple Interfacial Charge‐Transfer Bands. Issue 12 (16th January 2017) - Ndjawa, Guy O. Ngongang; Graham, Kenneth R.; Mollinger, Sonya; Wu, Di M.; Hanifi, David; Prasanna, Rohit; Rose, Bradley D.; Dey, Sukumar; Yu, Liyang; Brédas, Jean‐Luc; McGehee, Michael D.; Salleo, Alberto; et al.
Abstract : In organic solar cells (OSCs), the energy of the charge‐transfer (CT) complexes at the donor–acceptor interface, E CT, determines the maximum open‐circuit voltage ( V OC ). The coexistence of phases with different degrees of order in the donor or the acceptor, as in blends of semi‐crystalline donors and fullerenes in bulk heterojunction layers, influences the distribution of CT states and the V OC enormously. Yet, the question of how structural heterogeneities alter CT states and the V OC is seldom addressed systematically. In this work, we combine experimental measurements of vacuum‐deposited rubrene/C60 bilayer OSCs, with varying microstructure and texture, with density functional theory calculations to determine how relative molecular orientations and extents of structural order influence E CT and V OC . We find that varying the microstructure of rubrene gives rise to CT bands with varying energies. The CT band that originates from crystalline rubrene lies up to ≈0.4 eV lower in energy compared to the one that arises from amorphous rubrene. These low‐lying CT states contribute strongly to V OC losses and result mainly from hole delocalization in aggregated rubrene. This work points to the importance of realizing interfacial structural control that prevents the formation of low E CT configurations and maximizes V OC . Abstract : In organic solar cells, the coexistence of donor phases with different degrees of order influences the distribution of charge‐transfer (CT) states. Abrupt interfaces between aggregated donor and acceptor phases cause voltage loss as high as ≈300 mV. Interfacial mixing resulting in local disorder between aggregated phases should eliminate the low energy CT states and improve the open‐circuit voltage.